Assessing Local and National Government Interaction in LED: A Policy Evaluation of South Africa’s Metros - Soga, Babalwa; Vyas-Doorgapersad , Shikha (Mediterranean Journal of Social Sciences, 2021)
The article examined the adoption of the 2018-2028 National Framework for Local Economic Development (NFLED 2018-2028) in South Africa eight metropolitan municipalities. The article employs a qualitative research approach whereby a document analysis of municipality strategic reports reveals that there is low adoption of the National Framework for Local Economic Development in South African metros. The findings confirm that whilst metropolitan municipalities cannot be expected to share the exact policy adoption considerations due to their political, administrative, economic and demographic heterogeneity, it is suggested that there should be a balanced level of policy standardisation when it comes to LED and other municipal kep performance areas (KPAs). The article concludes that South Africa’s metropolitan municipalities had not adopted most of the five enabling pillars of the National Framework for LED 2018-2028 as part of the key performance areas (KPAs). This points to the discord between national LED policies and local level LED planning. While there is a need for LED planning decentralisation to meet local needs in metros, general alignment with national policies could assist in unlocking intellectual and financial resources that municipalities lack. Received: 23 September 2021 / Accepted: 25 October 2021 / Published: 5 November 2021